Hubungan peran keluarga tentang penanganan ispa dengan kejadian ispa berulang pada balita - Richta Puspita Haryanti; Isabel Angelica; Yuli Lestari (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Acute respiratory infections (ARI) are the leading cause of death in children under five worldwide, with a prevalence in Indonesia reaching 4.0% in 2023. This disease is often linked to environmental factors and a lack of family attention in its treatment. Purpose: To investigate the relationship between the role of the family in the treatment of ARI and the recurrence of ARI in children under five. Method: A correlational descriptive design with a cross-sectional approach was used. This study was conducted at Advent Hospital in Bandar Lampung. The study population consisted of children under five years of age who were treated for ARI. A total of 43 samples were taken using purposive sampling. The instrument used in this study was a family role questionnaire. Research subjects were selected based on specific criteria. Data analysis techniques used the Chi-square test. Results: The study found that most subjects were female, most were in the early adult age category, most had a high school education level, most were unemployed, and most had a poor family role in handling ARI. Most toddlers who had experienced recurrent ARI numbered 25 toddlers. Conclusion: Based on statistical analysis, it was found that there is a relationship between the role of the family in handling ARI and the incidence of recurrent ARI with a p-value <0.05. The positive role of the family is very important in the incidence of recurrent ARI in toddlers. Therefore, an education program is needed to increase knowledge and family involvement in handling ARI in toddlers.